2018
DOI: 10.1186/s12915-018-0563-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of males from mixed-sex societies in termites

Abstract: BackgroundSexual reproduction is the norm in almost all animal species, and in many advanced animal societies, both males and females participate in social activities. To date, the complete loss of males from advanced social animal lineages has been reported only in ants and honey bees (Hymenoptera), whose workers are always female and whose males display no helping behaviors even in normal sexual species. Asexuality has not previously been observed in colonies of another major group of social insects, the ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…We have recently reported asexual societies in a lineage of the termite Glyptotermes nakajimai (Isoptera: Kalotermitidae)a dramatic transition from mixed-sex to all-female asexual societies. This finding provides evidence that males are not indispensable in advanced animal societies, regardless of whether males engage in social activities or not [7].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…We have recently reported asexual societies in a lineage of the termite Glyptotermes nakajimai (Isoptera: Kalotermitidae)a dramatic transition from mixed-sex to all-female asexual societies. This finding provides evidence that males are not indispensable in advanced animal societies, regardless of whether males engage in social activities or not [7].…”
Section: Introductionmentioning
confidence: 72%
“…Lack of endosymbiotic bacteria in the asexual lineage of G. nakajimai (Table 1 and Figure 1) is suggestive of another selective force in the evolution of asexuality in the lineage. Indeed, Yashiro et al [7] have demonstrated that asexual colonies of G. nakajimai have a more uniform head size in their all-female soldier caste and fewer soldiers in proportion to other individuals compared with sexual colonies, indicating increased defensive efficiencies arising from asexuality. However, we are unable to rule out the possibility that endosymbiont DNA that causes parthenogenesis was integrated into the host genome, followed by the loss of the donor endosymbiont [14,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent evolution of thelytokous parthenogenesis (TP) in major clades is supported by different modalities of automixis: central fusion (CF), terminal fusion (TF) and gamete duplication (GD). Recently, the complete loss of males was reported in some populations of the Kalotermitidae Glyptotermes nakajimai , in which the mode of thelytoky, either automixis or apomixis, remains to be firmly demonstrated [44]…”
Section: Discussionmentioning
confidence: 99%
“…Thelytoky can occur via two principal modes: apomixis through which ploidy is maintained by mitosis and the resulting offspring are true clones of their mothers, and automixis which involves meiosis followed by ploidy restoration. In termites, apomixis was suggested in G. nakajimai (Yashiro et al 2018), while species with AQS use automixis. Furthermore, ploidy restoration under automixis occurs through different modalities among AQS species: terminal fusion in species of Reticulitermes, central fusion in Syntermitinae, and gamete duplication in Termitinae (Table 1).…”
Section: Genetic Consequences Of Asexual Queen Successionmentioning
confidence: 99%